Pelatihan Budidaya Tanaman Hortikultura untuk Optimalisasi Pekarangan di Nagari Taeh Bukik, Sumatera Barat - Nahda Kanara; Ritawati; Sentot Wahono; Trisia Wulantika; Chairunnisak; Rasdanelwati; Darmansyah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Horticulture plants are fruits, vegetables, flowers and ornamental plants, which are easy to cultivate in home gardens, could reduce household consumption expenditure and offer the good impact for family food security. Therefore, it is necessary to perform community training on horticulture technology by utilizing local resources. The purposes of this community service are to increase public awareness of the home garden’s existence and management, to increase the insight and knowledge of PKK members in horticultural crops cultivation, and to engage PKK members to practice horticulture cultivation in home garden. This community service was located in Taeh Bukik village, Limapuluh Kota Regency, West Sumatra from June‒September 2020. Methods of activities are audience, counseling, training, mentoring, while evaluation method are interview, observation, and survey to the trainees home gardens. This service, is moderately successful by being able to increase public awareness of the importance of the homegarden, increase the insight and knowledge of PKK members on horticulture cultivation, and PKK members were engage to practice horticulture cultivation in their own home garden, which is evidenced by the increase of plant diversity and plants arrangement practice in home gardens.